2020
DOI: 10.3390/bioengineering7020037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dual Cell Co-culture and Cell-conditioned Media on Yield and Function of a Human Olfactory Cell Line for Regenerative Medicine

Abstract: Olfactory ensheathing cells (OECs) are a promising candidate therapy for neuronal tissue repair. However, appropriate priming conditions to drive a regenerative phenotype are yet to be determined. We first assessed the effect of using a human fibroblast feeder layer and fibroblast conditioned media on primary rat olfactory mucosal cells (OMCs). We found that OMCs cultured on fibroblast feeders had greater expression of the key OEC marker p75NTR (25.1 ± 10.7 cells/mm2) compared with OMCs cultured on laminin (4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…This is the case for olfactory ensheathing cells (OECs), a promising therapy candidate for neuronal tissue repair. Rachael Wood and colleagues [ 8 ] showed that neither dual co-culture nor fibroblast-conditioned media support the regenerative human OEC phenotype, which means that the appropriate priming conditions to drive a regenerative phenotype in human OECs are yet to be determined.…”
mentioning
confidence: 99%
“…This is the case for olfactory ensheathing cells (OECs), a promising therapy candidate for neuronal tissue repair. Rachael Wood and colleagues [ 8 ] showed that neither dual co-culture nor fibroblast-conditioned media support the regenerative human OEC phenotype, which means that the appropriate priming conditions to drive a regenerative phenotype in human OECs are yet to be determined.…”
mentioning
confidence: 99%